Microlearning in Designing Data Mining Learning Course Material for Industrial Engineering Students - Aisyah Larasati; Rizqi Prayoga Editya; Benzfica Hanif Alfi Al Idrus; Vertic Eridani; Abdul Muid (Universitas Ngeri Malang, 2023)
Data mining is one of the core courses offered by the Industrial Engineering study program at the State University of Malang and the process applied at the State University of Malang is theoretical and practicum. The implementation of knowledge transfer can be done online or offline. Synchronous and asynchronous are the implementation of learning that is carried out online. The difference between the two lies in the implementation time. Synchronous classes will be conducted simultaneously even though it is hindered by the distance between students who are not in the same place. Asynchronous courses will hold classes at different times according to the students’ available time to access the material. The traditional or offline method is the implementation of face-to-face classes requiring the teachers and students to be at the same time and place and the teacher acts as a learning center. There are different learning methods that can be used to support knowledge transfer. Microlearning is a learning method that utilizes technological developments. The learning method offered is to use various interactive and communicative media to deliver the material. The media used are podcasts, presentation slides, infographics, e-modules, and videos that contain core discussions of the material. Data mining merupakan salah satu mata kuliah inti yang ditawarkan oleh program studi Teknik Industri Universitas Negeri Malang dan proses yang diterapkan di Universitas Negeri Malang adalah teori dan praktikum. Pelaksanaan transfer knowledge dapat dilakukan secara online maupun offline. Sinkron dan asinkron adalah pelaksanaan pembelajaran yang dilakukan secara daring. Perbedaan keduanya terletak pada waktu pelaksanaannya. Kelas sinkron akan dilakukan secara bersamaan meskipun terhalang oleh jarak antara siswa yang tidak berada di tempat yang sama. Kursus asinkron akan mengadakan kelas pada waktu yang berbeda sesuai dengan waktu yang tersedia siswa untuk mengakses materi. Metode tradisional atau luring adalah pelaksanaan kelas tatap muka yang mensyaratkan guru dan siswa berada pada waktu dan tempat yang sama serta guru berperan sebagai pusat pembelajaran. Ada berbagai metode pembelajaran yang dapat digunakan untuk mendukung transfer pengetahuan. Microlearning merupakan salah satu metode pembelajaran yang memanfaatkan perkembangan teknologi. Metode pembelajaran yang ditawarkan adalah dengan menggunakan berbagai media interaktif dan komunikatif untuk menyampaikan materi. Media yang digunakan adalah podcast, slide presentasi, infografis, e-modul, dan video yang berisi inti pembahasan materi.